Molecular anatomy of lymphocystis disease virus - Tidona, Christian; Darai, Gholamreza (Viral zoonoses and food of animal origin, 1997)
Lymphocystis disease (LD) has been reported to occur in over one hundred different species of fish worldwide. The disease is caused by lymphocystis disease virus (LCDV), a member of the iridovirus family. Numerous fish species that play an important role in fishery and fish farming are highly susceptible to LCDV infection. The infected animals develop disseminated clusters of aberrant hypertrophied cells within their connective tissue, the so-called lymphocystis cells. In the cytoplasm of these cells a massive accumulation of virions can be observed. As a first step towards understanding the mechanisms of viral infection and pathogenesis the complete genomic nucleotide sequence of lymphocystis disease virus type 1 (LCDV-1; flounder isolate) was determined. LCDV-1 is the type species of the genus Lymphocystivirus within the family Iridoviridae. The virions contain a single linear double-stranded DNA molecule that is circularly permuted, terminally redundant and heavily methylated. Since there is no convenient cell system for virus replication we determined the complete nucleotide sequence of the viral genome (102, 653 base pairs). Computer assisted analyses of 195 potential open reading frames resulted in the identification of a number of putative gene products with significant homology to functionally characterized proteins of other species.
Gesehen am 05.09.2024